Power Generation Using Energy Friendly Renewables Milieu (Wind Energy) - Runtuwene, Steven Johny; Pandelaki, Virnie M.; Mandagi, Jehuda J.J.; Kembuan, Rafael J.; Kaeng, Vanesa P. (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Power generation from fossil fuels has caused significant environmental problems including greenhouse gas emissions, air pollution, and climate change, which threaten global sustainability and human health. The increasing demand for clean energy solutions has made renewable energy technologies, particularly wind power, essential for addressing these environmental challenges. This research aims to explore the concept of more environmentally friendly power generation with a focus on reducing pollution and environmental impact through Wind Power Plants (PLTB). The study specifically analyzes the efficiency and performance of wind energy systems, examines their environmental benefits, and evaluates their implementation potential in Indonesia. In this study, different types of power generation technologies, particularly renewable energy sources such as wind, solar, hydro, and biomass, are compared to fossil fuel plants in terms of energy efficiency and pollutant emissions. The research methodology employs a comprehensive literature review approach, analyzing data from various scientific journals, technical reports, and energy policy documents from both national and international sources related to wind turbine technology and PLTB implementation in various countries. Results demonstrate that wind power plants can achieve energy conversion efficiency ranging from 35-45% with modern turbine technology, while producing zero greenhouse gas emissions during operation. The study reveals that Indonesia has significant wind energy potential, particularly in coastal areas of East Nusa Tenggara, South Sulawesi, and eastern islands, with average wind speeds of 6-7 m/s suitable for efficient PLTB operation. Results obtained show that the use of renewable energy can significantly lower CO2 emissions, with solar and wind energy being the most efficient options to reduce carbon footprint. The research concludes that PLTB implementation can reduce dependence on fossil fuels, provide long-term economic benefits through low operating costs, and contribute significantly to environmental sustainability. Overall, the application of environmentally friendly power plants is an effective solution to reduce pollution, support the sustainability of energy resources, and reduce dependence on fossil fuels.